2020
DOI: 10.1371/journal.pone.0237734
|View full text |Cite
|
Sign up to set email alerts
|

The cycle of distrust in health policy and behavior: Lessons learned from the Negev Bedouin

Abstract: Background Over the last decades, health systems worldwide have faced a decline in public trust. For marginalized minority populations, who generally suffer from poverty and political exclusion, the roots of this trend go much deeper, establishing a state of bi-directional distrust between them and health institutions. Although studied to a lesser extent compared to trust, distrust does impede health initiatives, such as infectious diseases prevention programs, mostly of so-called Neglected Zoonotic Diseases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…The Statnet Poll (2014) showed a genuine feeling of discrimination among the Arab community: 39% of respondents believe there is discrimination in Israeli institutions and 53% believe there is only partial equality. 28 Trust in governmental institutions is lower than for the Jewish population, 29 although trust in the health system was found to be higher among Arab compared with Jewish respondents in a survey. 30 The COVID-19 crisis was managed by collaboration between central government, local authorities and the MOH.…”
Section: Discussionmentioning
confidence: 98%
“…The Statnet Poll (2014) showed a genuine feeling of discrimination among the Arab community: 39% of respondents believe there is discrimination in Israeli institutions and 53% believe there is only partial equality. 28 Trust in governmental institutions is lower than for the Jewish population, 29 although trust in the health system was found to be higher among Arab compared with Jewish respondents in a survey. 30 The COVID-19 crisis was managed by collaboration between central government, local authorities and the MOH.…”
Section: Discussionmentioning
confidence: 98%
“…The Arab ethnic minority in Israel differs culturally and religiously from the Jewish majority, living typically in lower SES areas, more than half of them in the geographic periphery, and demonstrating poorer health outcomes compared with the general population [ 8 ]. Despite being hit harder especially in the second and third waves of the pandemic, vaccination uptake was low, which could be partly explained by a lower level of trust in governmental institutions, compared with the general population [ 19 ]. This pattern contrasts with routine childhood vaccinations in Israel, where rates are higher in the Arab compared to the Jewish population [ 20 ], but compares to research around the world where lower immunization rates were demonstrated in ethnic minorities and in low SES groups [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to assume that the main and perhaps only information source for Northern Bedouin mothers is the Ministry of Health. Studies have shown that Bedouin mothers usually take institutional health directives seriously and implement them regardless of their level of trust [ 89 , 90 ]. Moreover, despite this low level of trust in the system this group has a very high level of trust in doctors, making the family doctor’s recommendation a highly influential factor in mothers’ decision-making regarding vaccines.…”
Section: Discussionmentioning
confidence: 99%